Temporal Characteristics of Students as Cognitive Diagnostic Characteristics: The Context of Adaptive Education - Екатерина В. Бредун; Дмитрий Ю. Баланёв; Татьяна А. Ваулина; Ольга М. Краснорядцева; Элеонора А. Щеглова (Rossijskij psihologičeskij žurnal., 2020)
Introduction. The article presents the results of an experimental study of the individual temporal characteristics of cognitive space management in students while solving problems. Methods. The methodological tools are briefly described, including traditional test questionnaires for identifying temporal features of subjective perception of time (‘Semantic Time Differential’, ‘Time Perspective’), as well as modified and original research methods for identifying temporal characteristics of the cognitive activity of subjects in solving spatial problems in a laboratory experiment (‘Mental rotation’, ‘Accuracy’). Results. In a series of laboratory experiments, new research data were obtained on the temporal specificity of the process of constructing a personal cognitive space in students. Using prognostic modeling procedures, we were able to record the presence of structural relationships between the time perception, cognitive characteristics of problem-solving, and stability of academic performance. It was experimentally proved that characteristics of time reaction and effectiveness in completing accuracy tasks and mental rotation tasks act as temporal predictors of levels of students’ academic performance. Discussion. The study revealed the fact that students with a dominant temporal orientation toward the present situation, looking constantly for new stimuli and feelings in the current time, had quite pronounced deficits in the choice of educational strategies based on more long-term and well-defined objective in the future. It was noted, as an important aspect in the personalization of studying, that students must be aware of their own temporal, cognitive and other characteristics of the information processing, and manage on their own their educational environments as appropriate. The possibilities are discussed in using cognitive diagnostic characteristics to predict and timely correct individual trajectories of students’ educational paths as part of the adaptive approach to education.